PILIHAN RASIONALITAS ISTRI MENGGUGAT CERAI DI KECAMATAN TAPUNG KABUPATEN KAMPAR - Pertiwi, Heni Dwi; Marnelly, T. Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
At this time, in modern times and the increasing emancipation of women who have an influence on the changing mindsets of women today.  The change in mindset can be seen and proven from the high number of divorce today which is very much different from in the past.  When divorce used to be bad luck for women, now women have the courage to ask for divorce.  These changes do not just happen, awareness of the rights that are owned and that should be obtained, making women today more rational thinking.  From the rationality of these thoughts the women finally realized that there were discrepancies in their domestic life and chose to make divorce.  However, is the act of divorce always based on rationality?  Do not rule out the possibility of such actions based on non-rational.  So in this study, it will be seen how the household situation of women who do divorce, what causes the problem and the triggers of the problem, to make it a reason to sue for divorce, and whether the problems that are the reasons are rational, or maybe even non-rational. The research will involve 5 informants, and located in Tapung sub-district, Kampar Regency.  The method used is descriptive qualitative by conducting observations and in-depth interviews with 5 informants.  The results of this study indicate that the rational choice of suing for divorce is not always rational, because of the S informants in this study there are 2 informants who have a background problem that is the reason for traditional divorce and affection.   Keywords: Divorce, Rationality.